Morphologies, chemical compositions and optical properties of the hybrid gold core-platinum shell, Au@Pt, nanoparticles prepared by a simple reduction method were explored via a combination of transmission electron microscopy, energy dispersive X-ray spectroscopy and UV-visible spectrophotometry techniques. Various sizes of almost spherical and monodispersed Au@Pt core-shell nanoparticles were successfully achieved by changing of Au/Pt atomic ratios. The effect of Au/Pt atomic ratio on the electrocatalytic activities for these Au@Pt nanoparticles supported on multi-walled carbon nanotubes (MWCNTs) is revealed by cyclic voltammetry in 1.0 M H2SO4 + 2.0 M methanol aqueous solution. The maximum activity is obtained by using atomic ratio of Au/Pt at ~1. Moreover, all Au@Pt/MWCNTs catalysts exhibited higher activities than that of Pt/MWCNTs catalysts - Kontee Thongthai " (Science Faculty of Chiang Mai University, 2019)
Bimetallic nanoparticles